The study of the consumption process with a prominence of behavioral approach and its influence on the business units - Umer Qadir Sofi (Goodwood Publishing, 2019)
Purpose: Currently, the main question facing the entrepreneur is to find out who exactly the consumers of their goods what their market and its structure is. Owning such information, enterprises can direct their business activities in the right direction and achieve their goals. In this regard, the aim of the work is to study the effect of various characteristics on the consumption process. Research Methodology: The main method of research is monographic, and within the framework of the work a survey withheld conducted. Results: The main results of the study are related to the fact that the characteristics of the consumption process have a significant impact on the activities of business units. Keywords: Consumer process, Characteristics, Consumer groups. How to cite: Sofi, U.Q. (2019). Characteristics of the consumer process and influence it makes on the business with behavioral approach. International Journal of Financial, Accounting, and Management, 1(1), 57-68.